2013
DOI: 10.1021/es401171h
|View full text |Cite
|
Sign up to set email alerts
|

Bystander Effect between Zebrafish Embryos in Vivo Induced by High-Dose X-rays

Abstract: ABSTRACT:We employed embryos of the zebrafish, Danio rerio, for our studies on the in vivo bystander effect between embryos irradiated with highdose X-rays and naive unirradiated embryos. The effects on the naive whole embryos were studied through quantification of apoptotic signals at 25 h post fertilization (hpf) through the terminal dUTP transferase-mediated nick endlabeling (TUNEL) assay followed by counting the stained cells under a microscope. We report data showing that embryos at 5 hpf subjected to a 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 56 publications
0
13
0
2
Order By: Relevance
“…Choi et al [232] investigated the effect of carbon monoxide (CO) on the induction of the RIBE. More recently, the roles of NO and CO on the induction of the RIBE by high-dose X-ray irradiation in zebrafish embryos were also reported by Choi et al [52]. Considering the zebrafish embryo model as a good tumor model, the above results might be able to provide valuable information for Table 2 Key findings of non-targeted effects of ionizing radiation obtained using embryos of the zebrafish Danio rerio.…”
Section: Conclusion and Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Choi et al [232] investigated the effect of carbon monoxide (CO) on the induction of the RIBE. More recently, the roles of NO and CO on the induction of the RIBE by high-dose X-ray irradiation in zebrafish embryos were also reported by Choi et al [52]. Considering the zebrafish embryo model as a good tumor model, the above results might be able to provide valuable information for Table 2 Key findings of non-targeted effects of ionizing radiation obtained using embryos of the zebrafish Danio rerio.…”
Section: Conclusion and Discussionmentioning
confidence: 55%
“…It would also be interesting and beneficial to study whether the CF can be transmitted at the inter-organismic level. Recently, there has been massive evidence of the RIBE occurring at the inter-organismic level, e.g., between mice [50,51], zebrafish [52] and medaka [53].…”
Section: Definition and History Of The Ribementioning
confidence: 99%
“…Interestingly, previous research suggested that scavenging NO with cPTIO could suppress RIBE in the bystander zebrafish embryos [12]. Taken together, both scavenging NO from bystander embryos and adding exogenous NO to bystander embryos were anti-apoptotic.…”
Section: Discussionmentioning
confidence: 86%
“…In a previous in vivo study [12], we examined the influence of NO on the bystander effect between embryos of the zebrafish, Danio rerio , irradiated with high-dose X-rays and naive unirradiated embryos. We demonstrated that the RIBE between partnered irradiated and naïve unirradiated zebrafish embryos was suppressed through the addition of the NO scavenger 2-(4-carboxyphenyl)-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide (cPTIO) into the medium [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation